Ebook Marketplace as a Book Commercialization Strategy: Studies at HENBUK Digital Startups - Permana, I Putu Hendika (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Books are windows of knowledge. Book readers will gain broad insight and knowledge by reading various types of books. Technology is currently developing rapidly, so many book authors are currently selling books digitally. Digital books allow users to buy books online at lower prices than printed books. Indonesia has many book authors, but unfortunately the commercialization of books still faces many obstacles. This study uses a post-positivist paradigm with a qualitative approach and the type of research is descriptive. The unit of analysis is a digital startup Henbuk.com. In the research conducted, researchers will use this type of research by using narrative or descriptive research. The challenge to commercialize books is the background of this research. In this context, the hypothesis that can be used as a conjecture is that writers can take advantage of technological developments as a means of production, promotion and distribution of written works that are owned by many writers.